FAMILY FUNCTIONING AND BULLYING DYNAMICS AMONG ADOLESCENTS: A PHENOMENOLOGICAL STUDY IN INDONESIAN HIGH SCHOOLS (Pena Cendekia Insani, 2026)
Bullying remains a critical issue in educational settings, with increasing evidence highlighting the role of family environment in shaping adolescents’ social behavior. This study aims to explore the role of family functioning in both perpetrators and victims of bullying, as well as to examine the dynamics of bullying behavior among high school students in Medan, Indonesia. This research employed a qualitative phenomenological approach involving six primary participants and three triangulation informants selected through purposive sampling. Data were collected through in-depth interviews and observations, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that adolescents from dysfunctional family environments are more likely to engage in bullying behaviors. Conversely, effective family functioning serves as a protective factor that mitigates the negative impacts of bullying. The study also identifies that bullying behavior is influenced by both internal and external factors, characterized by power imbalance, repetitive aggressive actions, and perceived enjoyment by perpetrators. Furthermore, bullying produces significant psychological and social consequences not only for victims but also for perpetrators and bystanders. This study contributes to the understanding of bullying from a family systems perspective, emphasizing the importance of strengthening family functioning as a preventive strategy in educational contexts.